The single European market - a Schumpeterian event? - Horst Siebert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
It is now four years after the White Paper launched the project on the completion of the internal market [Commission, 1985]. 300 steps were packaged and sold in a manner by Delors and Lord Cockfield that "caught on". The basic strategy is simple: abolish or reduce market segmentations that still exist, facilitate free market access, as well as establish the free movement of people, goods, services, and capital (the so-called four freedoms). Will the single European market prove to be an institutional innovation - a Schumpeterian event in a region of the world that has been characterized by Eurosclerosis [ Giersch, 1985] and overreg ulation? Is Europe '92 an example of political entrepreneurship in the sense of Schumpeter and shall we see "new combinations of means of production" [Schumpeter, 1934, p. 74] being carried out? Or is Europe' 92 a "flash in the pan", flambe a la Delors, concocted by Cockfield, propagated by the press, public speeches and scientific conferences, but eventually dying from internal rent-seeking and protectionism?
Keywords: 330; EU-Binnenmarkt; EU-Staaten